2011
DOI: 10.3386/w17662
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Devaluations

Abstract: We show that even when the exchange rate cannot be devalued, a small set of conventional fiscal instruments can robustly replicate the real allocations attained under a nominal exchange rate devaluation in a dynamic New Keynesian open economy environment. We perform the analysis under alternative pricing assumptionsproducer or local currency pricing, along with nominal wage stickiness; under arbitrary degrees of asset market completeness and for general stochastic sequences of devaluations. There are two types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 15 publications
0
47
0
Order By: Relevance
“…Our paper is related to a recent paper by Farhi et al (2012) who establish a number of exact equivalence results between nominal exchange rate devaluations and fiscal devaluations. Farhi et al (2012) show that the particular combinations of the fiscal instruments which replicate the real allocations attained under a nominal exchange rate devaluation depend sensitively on features like alternative pricing assumptions and the degree of asset market incompleteness.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our paper is related to a recent paper by Farhi et al (2012) who establish a number of exact equivalence results between nominal exchange rate devaluations and fiscal devaluations. Farhi et al (2012) show that the particular combinations of the fiscal instruments which replicate the real allocations attained under a nominal exchange rate devaluation depend sensitively on features like alternative pricing assumptions and the degree of asset market incompleteness.…”
Section: Introductionmentioning
confidence: 85%
“…Farhi et al (2012) show that the particular combinations of the fiscal instruments which replicate the real allocations attained under a nominal exchange rate devaluation depend sensitively on features like alternative pricing assumptions and the degree of asset market incompleteness. The focus of our paper is somewhat different as we study under what assumptions, if at all, the fiscal reform undertaken by a member country of a monetary union can lead to quantitatively relevant effects.…”
Section: Introductionmentioning
confidence: 96%
“…Fahri, Gopinath and Itskhoki (2011) have shown that, when the exchange rate cannot be devalued, a particular tax combination can replicate the real effects attained under a nominal exchange rate devaluation. This is the idea behind the so called fiscal devaluation, that is, an increase of consumption taxes with an appropriate reduction of employers' social contributions, such that the fiscal budget remains unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Lipinska and von Thadden (2009), Franco (2011) and Farhi, Gopinath and Itskhoki (2011) provide quantitative evaluations of the effects of a tax change from direct to indirect taxes in general equilibrium models, whereas Franco (2011) and de Mooij and Keen (2012) provide empirical estimations on the effects on net exports, the former using an SVAR for the Portuguese economy and, the latter by means of a dynamic panel of 30 OECD countries from 1965 to 2009. Also consistent with these results, using an experimental economy, Riedl and Winden (2012) find that a shift from wages to consumption taxes improves economic performance, given the producers' reluctance to incur production costs up-front when facing product price uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…7 Farhi et al (2012) show that a simple combination of taxes can replicate nominal exchange rate policy, but they do not consider a Ramsey planner.…”
mentioning
confidence: 99%